ANALISIS SWOT KOMPONEN PARIWISATA KOTA BANDUNG - Ersy Ervina; Vany Octaviany (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This research aims to analyze tourism component in Bandung City which consist of tourism enterprises, tourism infrastructure & recreations, and tourism resources. This research uses descriptive qualitative method with data collection methods through observation, in-depth interviews, and literature study. Data analysis using SWOT analysis (Strength, Weakness, Opportunities & Treath) with weighting on each dimension of the tourism component. The results showed that tourism companies are very feasible and become the main supporting component. While there are still many infrastructure components that need to be addressed to support sustainable tourism activities. On the side of tourism resources, namely tourism is still very limited, the attraction of the city of Bandung is greatly supported by several tourist destinations in Bandung Regency and West Bandung Regency. The government and related stakeholders need to make a tourism packaging strategy in order to increase the attractiveness of Bandung in addition to shopping and culinary tourism.